Disaster capitalism. Issue 1 (May 2016) - SCHULLER, MARK; MALDONADO, JULIE K.
Abstract : The term "disaster capitalism, " launched in 2005 by activist journalist Naomi Klein, still has resonance within social movement circles. Yet its proliferation in media and social movements risks a confusion and weakening of the core concept and critiques. As anthropologists who value local communities' understanding of their own social world, how do we confront such a concept? What are our roles, both in clarifying and understanding the concept? More importantly, what is and should be our praxis, our responses to stemming the worst abuses of disaster capitalism? This chapter presents a sketch of a definition and model for disaster capitalism, followed by examples from ethnographic work on the 2010 earthquake in Haiti and the 2010 British Petroleum (BP) Deepwater Horizon Oil Disaster in the Gulf of Mexico to illustrate the phenomenon of disaster capitalism in practice. We follow this with discussions of the limitations of the disaster capitalism concept and the roles of anthropologists in confronting the issue.